2007
DOI: 10.1152/ajpheart.00288.2007
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of endogenous nitric oxide in angiotensin II-induced activation of vascular mitogen-activated protein kinases

Abstract: Angiotensin II (ANG II) is a powerful activator of mitogen-activated protein (MAP) kinase cascades in cardiovascular tissues through a redox-sensitive mechanism. Nitric oxide (NO) is considered to antagonize the vasoconstrictive and proarteriosclerotic actions of ANG II. However, the role of endogenous NO in ANG II-induced redox-sensitive signal transduction is not yet clear. In this study using catheterized, conscious rats, we found that acute intravenous administration of NG-nitro-l-arginine methyl ester (l-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2008
2008
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
1
4
1
Order By: Relevance
“…These findings suggest an inhibitory influence of NO on MAPK signaling that, when ablated, allows for a more robust response to inflammatory stimuli. Consistent with our observations, NO was recently shown to negatively regulate angiotensin II-elicited MAPK phosphorylation in vascular SMCs and in vivo, and exogenous peroxynitrite decreased phosphorylation of ERK1/2 and p38 in vascular SMCs (4,54,55). On the other hand, previous studies have also shown a stimulatory or biphasic role of NO-cGMP signaling on MAPK signaling (2,27,49).…”
Section: Discussionsupporting
confidence: 92%
“…These findings suggest an inhibitory influence of NO on MAPK signaling that, when ablated, allows for a more robust response to inflammatory stimuli. Consistent with our observations, NO was recently shown to negatively regulate angiotensin II-elicited MAPK phosphorylation in vascular SMCs and in vivo, and exogenous peroxynitrite decreased phosphorylation of ERK1/2 and p38 in vascular SMCs (4,54,55). On the other hand, previous studies have also shown a stimulatory or biphasic role of NO-cGMP signaling on MAPK signaling (2,27,49).…”
Section: Discussionsupporting
confidence: 92%
“…Studies have demonstrated that the formation of superoxide via NADPH oxidase activation by Ang II reduces NO production [30,31]. But, another study has reported that L-NAME suppresses Ang II-induced ROS formation in rat vascular smooth muscle cells [32]. Interestingly, we found that NO synthesis was not altered by Ang II, and that L-NAME did not suppress the Ang II-induced ROS formation in HaCaT cells.…”
Section: Discussioncontrasting
confidence: 61%
“…Tempol markedly suppressed Ang II-induced activation of vascular extracellular signal-regulated kinase (ERK) 1 and 2 and p38 (Zhang et al, 2007). This suppression was ascribed in part to an increase in NO bioactivity because it was prevented by NOS blockade (Zhang et al, 2007).…”
Section: Mechanistic Basis Of the Blood Pressure-lowering Effect mentioning
confidence: 99%
“…Tempol markedly suppressed Ang II-induced activation of vascular extracellular signal-regulated kinase (ERK) 1 and 2 and p38 (Zhang et al, 2007). This suppression was ascribed in part to an increase in NO bioactivity because it was prevented by NOS blockade (Zhang et al, 2007). Tempol prevented the phosphorylation of MAPKs, ERK1 and 2, c-Jun N-terminal kinase (JNK), and p38 in the aorta and heart of rats during infusions of Ang II or phenylephrine (PE) (Zhang et al, 2004a; Kimura et al, 2005a) and inhibited the phosphorylation of p38, MAPK, JNK, and ERKs in vascular tissue stimulated by Ang II or endothelin-1 (ET-1) (Touyz et al, 2004).…”
Section: Mechanistic Basis Of the Blood Pressure-lowering Effect mentioning
confidence: 99%